College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 1 - Equations and Inequalities - Exercise Set 1.2 - Page 119: 87



Work Step by Step

Solving for $x$ $\frac{3(x+3)}{5}= 2x+6$ Multiplying both sides by $5$ $5(\frac{3(x+3)}{5})=5( 2x+6)$ $3x+9= 10x+30$ $3x-10x=30-9$ $-7x= 21$ $x=-3$ Solving for $y$ $-2y-10= 5y+18$ $-2y- 5y=10+18$ $-7y=28$ $y=-4$ Substituting $x$ and $y$ values in $x^{2}-(xy-y) = (-3)^{2}-((-3 \times -4)-(-4))$ $= 9-(12+4)$ $= 9-16$ $=-7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.